Theory-Based Approach to Research Question Formulation: Fundamentals for Postgraduate Students - Major Elazia, Paul; Manya, Stephen; Ngugi, Margaret; Nangila Makhokha, Arnety; Wisindi, Andrew; Amateshe, Maurice; Bah, Saidou; Shinachi Wanyonyi, Michael (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Postgraduate students are required to undertake research projects as part of the requirements of the courses they take. In that regard, they need to understand how theories are applied in research work. The aim of this study was to document challenges postgraduate students encounter when applying social research theories in constructing research questions. The key objective was to determine the deficits postgraduate students have in applying theories in the formulation of research questions. The second objective was to identify appropriate strategies as proposed from the respondents in overcoming the deficits identified under the first objective. Thestudy was conducted in Kenya and Armenia in selected public universities. A Quasi-qualitative survey research design was used and target population consisted of lecturers and postgraduate students conveniently selected from the social sciences departments. Focused group discussions (FGD) were used to collect data through the online platform Zoom where one FGD consisted of 9 conveniently selected postgraduate supervisors and two consisted of 11 and 14 postgraduate students respectively. Internet-based research was used to get information from online sources. Thematic and contextual analyses were used and the results showed that students have inadequate skills, knowledge, and competencies suitable for helping them formulate research questions using theoretical constructs. The study recommends improving the content and approaches of teaching research methods, focusing on the application of theory in research studies. The study further proposes strategies for ensuring that the students can design, develop, and use theory in all aspects of conducting research. The study has value by proposing ways of overcoming inadequacies by improving postgraduate students’ research competencies, by applying theoretical constructs in the development of research questions for their research studies.